Women who prefer longer penises are more likely to have vaginal orgasms (but not clitoral orgasms): Implications for an evolutionary theory of vaginal orgasm - Costa, Rui Miguel (2012)
Introduction. Research indicates that (i) women’s orgasm during penile–vaginal intercourse (PVI) is influenced by fitness-related male partner characteristics, (ii) penis size is important for many women, and (iii) preference for a longer penis is associated with greater vaginal orgasm consistency (triggered by PVI without concurrent clitoral masturbation). Aims. To test the hypothesis that vaginal orgasm frequency is associated with women’s reporting that a longer than average penis is more likely to provoke their PVI orgasm. Method. Three hundred twenty-three women reported in an online survey their past month frequency of various sexual behaviors (including PVI, vaginal orgasm, and clitoral orgasm), the effects of a longer than average penis on likelihood of orgasm from PVI, and the importance they attributed to PVI and to noncoital sex. Main Outcome Measures. Univariate analyses of covariance with dependent variables being frequencies of various sexual behaviors and types of orgasm and with independent variable being women reporting vs. not reporting that a longer than average penis is important for their orgasm from PVI. Results. Likelihood of orgasm with a longer penis was related to greater vaginal orgasm frequency but unrelated to frequencies of other sexual behaviors, including clitoral orgasm. In binary logistic regression, likelihood of orgasm with a longer penis was related to greater importance attributed to PVI and lesser importance attributed to noncoital sex. Conclusions. Women who prefer deeper penile–vaginal stimulation are more likely to have vaginal orgasm, consistent with vaginal orgasm evolving as part of a female mate choice system favoring somewhat larger than average penises. Future research could extend the findings by overcoming limitations related to more precise measurement of penis length (to the pubis and pressed close to the pubic bone) and girth, and large representative samples. Future experimental research might assess to what extent different penis sizes influence women’s satisfaction and likelihood of vaginal orgasm.